Experimental and Computational Investigation on Colistin-mediated Fluorescence Labelling of Bacterial Lipopolysaccharide - Saurodeep Mandal; Dipanwita Patra; Sukhendu Mandal; Gourab Kanti Das; Prithidipa Sahoo (Recent Developments in Chemistry and Biochemistry Research Vol. 9, 2024)
Gram-negative bacteria are among the world’s most significant public health problems due to their high antibiotic resistance. These microorganisms have substantial clinical importance due to their high risk and lead to high morbidity and mortality. Gram-negative bacterial infections are becoming untreatable due to their ability to mutate and the gradual development of resistance against available antimicrobials. In recent times colistin, a drug of last resort started losing its efficacy towards multidrug-resistant bacterial infections. Colistin targets bacterial endotoxin lipopolysaccharide (LPS) and destabilizes the cytoplasmic membrane by disrupting the outer LPS membrane. In this chapter, the bacterial LPS, the main constituent of the cytoplasmic membrane of bacterial cells has been manifested to comprehend the interaction pattern of LPS with colistin. The chemosensor NAF has been synthesized to selectively recognize colistin and be able to spot LPS with its “turn-on” fluorescence signals. The computationally derived three-dimensional structure of LPS has been introduced to speculate the mode of possible binding of colistin with LPS and has also been thoroughly studied with the help of quantum mechanical calculations and molecular dynamics energy minimization. Fluorescence microscopy and FE-SEM microscopic studies also help in observing the change in structural morphology of colistin-sensitive and resistant Salmonella typhi in different experimental conditions.